Dipole Moment‐ and Molecular Orbital‐Engineered Phosphine Oxide‐Free Host Materials for Efficient and Stable Blue Thermally Activated Delayed Fluorescence (Adv. Sci. 3/2022). Issue 3 (25th January 2022) - Ihn, Soo‐Ghang; Jeong, Daun; Kwon, Eun Suk; Kim, Sangmo; Chung, Yeon Sook; Sim, Myungsun; Chwae, Jun; Koishikawa, Yasushi; Jeon, Soon Ok; Kim, Jong Soo; Kim, Joonghyuk; Nam, Sungho; et al.
Abstract : Organic Light‐Emitting Diodes In many thermally activated delayed fluorescence (TADF) organic light‐emitting diodes (OLEDs), efficiency and lifespan have shown a trade‐off relationship. In article number 2102141, Soo‐Ghang Ihn and coworkers present phosphine oxide‐free hosts designed via a dipole moment‐ and molecular orbital‐engineering, which enhance the device efficiency and stability simultaneously. This approach paves the way for the commercialization of TADF OLED technology.